A study on material removal rate during EDM with tantalum carbide-copper compacted electrode - Khan, Ahsan Ali; Mohd Hambiyah, Mohammad Azhadi; Nazi Nadin, Mohd Faiz (International Islamic University Malaysia, 2011)
Abstract. Powder metallurgy compacted electrodes are now being used in many cases for some special purposes. These special electrodes play an important role in material removal rate, work surface finish, electrode wear, etc. In the present work EDM was performed with tantalum carbide and copper mixed compacted electrodes. Experimental results show that material removal rate during EDM with TaC-Cu electrode is lower compared to that with solid copper electrode.